Competitive and complimentary effects of Artemisia ( Artemisia annua L.) on Maize ( Zea mays L . ) intercrops in a sub - humid ecozone of Western Kenya - Chumba, RKB; Owuor, B; Mwai, GN; Andika, DO (Ministry of Agriculture, Vihiga County, K enya, 2013)
An agroforestry (AF) study at Maseno, Western Kenya investigated some component interactions in a shrub-based inter cropping system of artemisia (Artemisia annua L.) and maize (Zea MaysL.) for two consecutive rainfed seasons, by evaluating yield attributes and patterns from among different spacing regimes using the competitive ratio(CR) and % Land Use Efficiency (LUE). The experiment had 8 treatments (T1to T8) laid out in a randomized complete block design (RCBD) with 3 replications. The treatments had a significant effect (P < 0.05) on plant biomass of maize and LUE. There was also a significant effect (P<0.05) on CR of artemisia against maize among the intercrops. Artemisia as an Asteraceae is 1.3 (or 30%) more competitive than maize (Graminae), when the two component crops are grown in association with optimal spacing. LUE values higher that 100% indicate the presence of facilitative component interactions or complementarity among the crop components of T3 T4andT6. It is concluded that by varying spacing regimes and hence plant densities for biomass and leaf yields of maize and artemisia respectively, profitable artemisia+maize intercropping require that farmers apply spatial arrangements in which complementarity effects on net yields equal or exceed competitive abilities of artemisia. In so doing, the spacing regimes of T4= Artemisia 0.75m X 0.75m;Maize 0.9m X 0.75mand T6= Artemisia 0.9m X 0.9m; Maize 0.9m X 0.75m are recommended for the purpose.
Abstract
Keywords: Agroforestry; Competitive ratio; Land use efficiency; Artemisia; Maize